Foundry 4.0: Revolutionizing Casting Production with Computerized Systems - T.R. Vijayaram (International Journal of Machine Systems and Manufacturing Technology, 2024)
For a considerable amount of time, foundries used computers for handling inventory, waging, wages, accounting, personnel records, and quality control. Nearly all of the foundry's systems and machinery are computerized. Through the installation of computers in foundries, employees' workloads and levels of stress have reduced significantly, and the workplace feeling has greatly improved. This review paper explores the potential implications and functions of computers in foundries. A thorough explanation of foundry software programs and epert systems is provided for the metal casting industry. To assist with understanding each foundry software package's distinctive use, a table featuring software programs produced by the American Foundrymen's Society (AFS) is given.
Keywords: AFS foundry software packages; Foundry mechanization; computer aided foundry model; computerized foundry line; expert systems; numerical simulation